Political economy of informal housing scenario in Sebeta, Furi, and Gelan Guda subcity of Sheger City, Oromia, Ethiopia - Efa Tadesse Debele; Taye Negussie (Research in Globalization, 2023)
Access to housing is a fundamental necessity for individuals. Even though the motives of informal housing are complex, analyzing the issue from a political economy perspective needs to be adequately addressed. This study analyzed why informal housing continues and is challenging to eradicate. It motivated researchers to understand the phenomenon from a political economy approach, assuming it offers a holistic understanding. A mixed research design was adopted by considering the nature of the problem and the research objectives intended to be achieved. Three hundred eighty-four respondents were randomly selected to substantiate research questions. Empirical findings indicated that informal housing had become the prevailing housing market. Researchers identified that the motives of speculators, the shelter needs of individuals, the motives of brokers, the interests of farmers, and the level of structural hospitality are significantly associated with the prevalence of informal housing. However, gain motives, need motives, and structural hospitalities were significant variables that significantly predicted the intensity and prevalence of informal housing. In contrast, brokers' motives and farmers' cooperation did not significantly predict the informal housing scenario. Thus, prospective intervention is expected to reverse the scenario by implementing a political economy analysis-based intervention framework, expanding adequate, affordable housing for the urban low-income people who need shelter, developing land and housing database to reduce structural hospitality, and taking proactive measures against the structural actors who are rent-seekers and exploited opportunities of informal housing. Furthermore, researchers seek to analyze informal housing issues in a political economy approach to understand the problem holistically.
Keywords: 330; Informal housing; Political economy; Sheger City; Shelter; Speculation; Structural